SDG11 sustainable cities and communities : towards inclusive, safe, and resilient settlements - Al-Zu'bi, Maha; Radović, Vesela (Concise guides to the United Nations sustainable development goals, 2018)
Sustainable Development Goal 11, one of 17 Global Goals that make up the 2030 Agenda for Sustainable Development, recognizes the need to make cities and human settlements 'inclusive, safe, resilient and sustainable.' This book uses empirical analysis to address challenges associated with the implementation of SDG11. It considers policies, strategies and success stories from various regions, countries and cities, including actions to improve natural resources management, reduce GHG emissions, and develop urban adaptation and resilience strategies and disaster risk management to help decision-makers, planners and practitioners in achieving the 2030 agenda. Concise Guides to the United Nations Sustainable Development Goals comprises 17 short books, each examining one of the UN Sustainable Development Goals. The series provides an integrated assessment of the SDGs from economic, legal, social, environmental and cultural perspectives.